Meat Shrinkage - Leising, J.; Tuma, H. (Kansas State University. Agricultural Experiment Station, 2011)
Meat shrinkage is a major problem for the beef industry. Shrinkage (loss in weight) results from many factors: improper chilling, low humidity, not packaging, poor sanitation, or excessive ageing time. Most beef is chilled overnight (16-20 hrs.) at cooler temperatures of 25 to 40 ̊F. internal temperatures after 20 hours chill vary from 55 ̊to 70 ̊F depending on cooler conditions and carcass weight. During a normal chill cycle, beef carcasses shrink 6 to 12 pounds or 1-2% for 600-pound carcass with the shrink depending on many cooler and carcass factors. Various methods have been used to reduce moisture evaporation (shrink) by protecting the meat with a bag or wrapper and by controlling temperature and relative humidity. Information is limited concerning optimum chilling condition for maximum cooling efficiency with minimum shrinkage.
Keywords: Beef; Meat shrinkage; Carcass weight; Temperature